Automatic silicon nitride pulping process

Through the automated silicon nitride pulping process, the problem of raw material waste caused by the prone to adherence of silicon nitride slurry is solved, and high-flowability and high utilization rate silicon nitride slurry is prepared, which improves production efficiency.

CN119797934APending Publication Date: 2025-04-11YANGZHOU XIAOTIAN PHOTOSKOT TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510006314.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-03
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

During the preparation of silicon nitride substrates, traditional pulping methods cause silicon nitride slurry to easily adhere to the reactor, resulting in uneven mixing and waste of raw materials.

Method used

An automated silicon nitride pulping process is adopted to remove surface impurities on the silicon nitride powder and add solvents, dispersants, binders, defoamers, etc., and through sand milling, vertical stirring and defoaming processes, a high-flow and high-utility silicon nitride slurry is prepared.

Benefits of technology

It effectively improves the fluidity and raw material utilization rate of silicon nitride slurry, reduces waste of raw materials, and improves production efficiency through process automation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005226967910000111
    Figure BDA0005226967910000111
  • Figure BDA0005226967910000121
    Figure BDA0005226967910000121
Patent Text Reader

Abstract

The invention relates to the technical field of ceramic materials, in particular to an automatic silicon nitride pulping process. Then, 100-130 parts of silicon nitride powder, 4-8 parts of a sintering aid, 7.6-9 parts of a binder, 3.3-4.7 parts of a dispersing agent, 1-2 parts of a defoaming agent, 55-67 parts of a solvent and 4-7 parts of a plasticizer are uniformly mixed and sequentially subjected to sanding, vertical stirring and defoaming processes, and the silicon nitride slurry with high fluidity and high utilization rate is obtained, on one hand, the dispersion characteristic of polyvinylpyrrolidone is achieved; on the other hand, the modified polyvinylpyrrolidone is a block copolymer, self-assembly can be induced by incompatibility among different blocks of the modified polyvinylpyrrolidone, then the overall fluidity of the slurry and the utilization rate of raw materials can be effectively improved, and compared with the prior art, the modified polyvinylpyrrolidone has wide application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of ceramic materials, and in particular to an automated silicon nitride slurry making process. Background Art

[0002] With the rapid development of science and technology such as energy, space technology, new energy power, and high-speed rail and ground transportation, the demand for high-power power electronic devices is increasing day by day. The substrate is the core component of the integrated circuit of power electronic devices. Under complex and harsh conditions of use, the reason that affects the stability of the substrate is the combined effect of extreme heat and mechanical stress. The existing substrate materials are difficult to have good thermal shock resistance and mechanical strength. Therefore, there is an urgent need for materials with excellent thermal conductivity and mechanical properties to be used in the field of substrate manufacturing.

[0003] Silicon nitride, with the chemical formula Si3N4, is an inorganic non-metallic strong covalent bond compound and an important structural ceramic material. It is a superhard material that has lubricity and wear resistance, and is an atomic crystal; it resists oxidation at high temperatures. It can also resist thermal shocks, and will not break even if it is heated to more than 1000°C in the air, cooled rapidly, and then heated rapidly. It is precisely because of the excellent properties of silicon nitride ceramics that they are often used to manufacture mechanical components such as bearings, turbine blades, mechanical seal rings, and permanent molds.

[0004] Silicon nitride ceramics are precision ceramics sintered at high temperature in a non-oxidizing atmosphere. They have the advantages of high strength, high wear resistance, high temperature resistance, corrosion resistance, acid and alkali resistance, oxidation resistance and wear resistance. Therefore, they have special use value in working environments with high temperature and high-strength corrosive media. They can be used in seawater for a long time and have good electrical and magnetic insulation properties. They are very suitable for the application of power modules of high-power power electronic devices. Silicon nitride substrates with high thermal conductivity and high mechanical strength (bending strength and fracture toughness) can have a longer service life and higher reliability in harsh working environments, making electronic power systems safer and more reliable during operation.

[0005] In the preparation process of silicon nitride substrates, the pulping process is also very important. Traditional pulping methods include mechanical pulping, chemical pulping and organic solvent pulping. However, in these methods, silicon nitride slurry is easy to adhere to various reactors, resulting in uneven mixing and thus causing a large amount of raw material waste. That is, the utilization rate of raw materials in the silicon nitride pulping process needs to be improved.

[0006] Therefore, according to the above-mentioned related technologies, it is urgent to develop an automated silicon nitride slurry making process. Summary of the invention

[0007] In view of this, the purpose of the present invention is to propose an automated silicon nitride slurry preparation process to solve the problem of easy waste of raw materials in the silicon nitride slurry preparation process in the prior art.

[0008] Based on the above objectives, the present invention provides an automated silicon nitride slurry making process.

[0009] An automated silicon nitride slurrying process comprises the following raw materials in parts by weight:

[0010] Silicon nitride powder 100-130 parts, sintering aid 4-8 parts, binder 7.6-9 parts, dispersant 3.3-4.7 parts, defoamer 1-2 parts, solvent 55-67 parts, plasticizer 4-7 parts;

[0011] The dispersant is modified polyvinyl pyrrolidone;

[0012] The modified polyvinyl pyrrolidone is prepared from polyvinyl pyrrolidone, beta-mercaptoethanol, S, S'-di(alpha, alpha'-dimethyl-alpha"-acetic acid) trithiocarbonate and styrene.

[0013] Preferably, the particle size of the silicon nitride powder is 1.6-3.3 μm;

[0014] The sintering aid is at least one of aluminum oxide, yttrium oxide, magnesium oxide, calcium oxide and magnesium silicon nitrogen;

[0015] The solvent is at least one of ethanol, ethylene glycol, isopropanol, n-butanol, and 2-butanone;

[0016] The binder is selected from at least one of polyethylene glycol, polyvinyl butyral, and methyl acrylate;

[0017] The plasticizer is any one of phthalate, polyethylene glycol and glycerol;

[0018] The defoaming agent is any one of fatty alcohol polyoxyethylene ether, alkylphenol polyoxyethylene ether and polydimethylsiloxane.

[0019] Preferably, the preparation method of the modified polyvinyl pyrrolidone is as follows:

[0020] Step A1. Add isopropanol and 2,2'-azo[2-methyl-N-(2-hydroxyethyl)propionamide] to polyvinyl pyrrolidone, and add one-third of β-mercaptoethanol at the beginning of the reaction and after 20 minutes and 40 minutes, respectively, and heat under reflux at 80-88°C for 2-3 hours to obtain a mixture A;

[0021] Step A2. Mix the mixture A with S, S′-di(α, α′-dimethyl-α″-acetic acid) trithiocarbonate and dicyclohexylcarbodiimide, and heat under reflux to obtain a mixture B;

[0022] Step A3. Mix mixture B, styrene, maleic anhydride and azobisisobutyronitrile, and heat under reflux at 50-60° C. for 3-4 hours to obtain modified polyvinyl pyrrolidone.

[0023] Preferably, in step A1, the usage ratio of polyvinyl pyrrolidone, isopropanol, 2,2'-azo[2-methyl-N-(2-hydroxyethyl)propionamide] and β-mercaptoethanol is 1 mol: 20-25 mL: 10 g: 0.03-0.04 mol.

[0024] Preferably, in step A2, the mass ratio of the mixture A to S,S′-di(α,α′-dimethyl-α″-acetic acid) trithiocarbonate and dicyclohexylcarbodiimide is 20-23:15-18:20-25;

[0025] The temperature during the heating reflux is 35-40° C. and the time is 50-70 min.

[0026] Preferably, in step A3, the mass ratio of the mixture B, styrene, maleic anhydride and azobisisobutyronitrile is 50-60:13-15:22-26:0.01-0.03.

[0027] Preferably, the automated silicon nitride slurrying process comprises the following steps:

[0028] Step S1. The silicon nitride powder is pickled with a mixed acid of nitric acid, hydrochloric acid and sulfuric acid for 2-4 hours, then washed with water three times, filtered and dried at 40-50°C to obtain the treated silicon nitride powder;

[0029] Step S2. The treated silicon nitride powder is mixed with a sintering aid, a dispersant, a defoaming agent, and a solvent and stirred evenly, and then sent to a sand mill for sand grinding to obtain a mixture C;

[0030] Step S3. Step S3. Dissolve polyvinyl butyral in a toluene-ethanol mixed solution with a volume ratio of 1:4-6 to obtain a binder, then feed the mixture C into a vertical mixer, add the binder and the plasticizer, set the stirring parameters, and fully stir the slurry to obtain a mixture D;

[0031] Step S4: sending the mixture D into an online degassing machine for degassing to obtain silicon nitride slurry.

[0032] Preferably, the volume ratio of nitric acid, hydrochloric acid and sulfuric acid in step S1 is 10-20:60-80:10-20;

[0033] The mass fraction of the nitric acid is less than 68%, the mass fraction of the hydrochloric acid is less than 20%, and the mass fraction of the sulfuric acid is less than 70%.

[0034] Preferably, the speed of the sand mill in step S2 is 720-830 r / min;

[0035] During the sand grinding, silicon nitride grinding balls with a diameter of 0.6-0.68 mm are added, and the sand grinding time is 55-70 minutes.

[0036] Preferably, the stirring rate in the stirring parameters in step S3 is 400-600 r / min, and the stirring time is 2-3 h;

[0037] The vacuum degree during degassing in step S4 is 0.1-0.5 Pa, the temperature is 45-55° C., the stirring rate is 600-800 r / min, and the degassing time is 100-120 min.

[0038] Beneficial effects of the present invention:

[0039] The present invention provides an automated silicon nitride slurry preparation process. The present invention removes impurities from the surface of silicon nitride powder, adds a solvent, a dispersant, a binder, and a defoaming agent, and performs sand milling, vertical stirring, and a defoaming process to obtain a silicon nitride slurry with high fluidity and high utilization rate.

[0040] Among them, the dispersant is modified polyvinyl pyrrolidone, which has the dispersing characteristics of polyvinyl pyrrolidone on the one hand. The imide group contained in polyvinyl pyrrolidone has strong polarity, shows good adsorption capacity for solid particles, and is widely used in powder dispersion; on the other hand, the modified polyvinyl pyrrolidone is a block copolymer, and the incompatibility between its different blocks can induce self-assembly, thereby improving the dispersibility and stability of the material, and then effectively improving the overall fluidity of the slurry and the utilization rate of raw materials. Compared with the existing technology, it has broad application prospects. DETAILED DESCRIPTION

[0041] In order to make the objectives, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with specific embodiments.

[0042] The sources and properties of some of the raw materials used in the present invention are as follows:

[0043] Isopropanol was purchased from Lihua Yiweiyuan Chemical Co., Ltd.; 2,2'-azo[2-methyl-N-(2-hydroxyethyl)propionamide] was purchased from Guangzhou Yuanda New Materials Co., Ltd.; β-mercaptoethanol was purchased from Guangdong Zhonghe Chemical Plastics Co., Ltd.; S,S'-bis(α,α'-dimethyl-α"-acetic acid) trithiocarbonate was purchased from Yingkou Hengyang New Energy Chemical Co., Ltd.; dicyclohexylcarbodiimide was purchased from Shandong Dibeck Bioengineering Co., Ltd.; styrene was purchased from Wanhua Chemical; maleic anhydride was purchased from Shandong Qiangsen Chemical Co., Ltd.; azobisisobutyronitrile was purchased from Anda Jiacheng Chemical Co., Ltd.

[0044] Embodiment 1: An automated silicon nitride slurrying process, comprising the following steps:

[0045] S1. Add 20 mL of isopropanol and 10 g of 2,2'-azo[2-methyl-N-(2-hydroxyethyl)propionamide] to 1 mol of polyvinylpyrrolidone, and add one third of β-mercaptoethanol at the beginning of the reaction and after 20 minutes and 40 minutes, respectively. The total amount of β-mercaptoethanol is 0.03 mol. Heat and reflux at 80°C for 2 hours to obtain a mixture A;

[0046] S2. 20 g of mixture A was mixed with 15 g of S, S′-di(α, α′-dimethyl-α″-acetic acid) trithiocarbonate and 20 g of dicyclohexylcarbodiimide, and heated under reflux at 35-40° C. for 50 min to obtain a mixture B;

[0047] S3. 50 g of mixture B, 13 g of styrene, 22 g of maleic anhydride and 0.01 g of azobisisobutyronitrile were mixed and heated under reflux at 50 ° C for 3 h to obtain a modified polyvinyl pyrrolidone;

[0048] S4. The silicon nitride powder was pickled with a mixed acid of 10 mL nitric acid, 80 mL hydrochloric acid and 10 mL sulfuric acid for 2 h, wherein the acid mass fraction was less than 68%, the hydrochloric acid mass fraction was less than 20%, and the sulfuric acid mass fraction was less than 70%, then washed 3 times with water, filtered and dried at 40 ° C to obtain the treated silicon nitride powder;

[0049] S5. 100 g of the treated silicon nitride powder was mixed with 4 g of alumina, 3.3 g of modified polyvinyl pyrrolidone, 1 g of polydimethylsiloxane, and 55 g of ethanol and stirred uniformly, and then sent to a sand mill for sand milling, the sand mill speed was set to 720 r / min, and silicon nitride grinding balls with a diameter of 0.6 mm were added, and the sand milling time was 55 min to obtain a mixture C;

[0050] S6. The polyvinyl butyral was dissolved in a toluene-ethanol mixed solution with a volume ratio of 1:4 to obtain a binder, and then the mixture C was fed into a vertical mixer, 7.6 g of the binder and 4 g of phthalate were added, the stirring rate was 400 r / min, the stirring time was 2 h, and the slurry was fully stirred to obtain a mixture D;

[0051] S7. The mixture D is sent to an online degassing machine for degassing. The vacuum degree during degassing is 0.1 Pa, the temperature is 45° C., the stirring rate is 600 r / min, and the degassing time is 100 min to obtain silicon nitride slurry.

[0052] Embodiment 2: An automated silicon nitride slurrying process comprising the following steps:

[0053] S1. Add 22 mL of isopropanol and 10 g of 2,2'-azo[2-methyl-N-(2-hydroxyethyl)propionamide] to 1 mol of polyvinylpyrrolidone, and add one third of β-mercaptoethanol at the beginning of the reaction and after 20 minutes and 40 minutes, respectively. The total amount of β-mercaptoethanol is 0.033 mol. Heat and reflux at 83°C for 2.5 hours to obtain a mixture A;

[0054] S2. 21 g of mixture A was mixed with 16 g of S, S′-di(α, α′-dimethyl-α″-acetic acid) trithiocarbonate and 22 g of dicyclohexylcarbodiimide, and heated under reflux at 38° C. for 60 min to obtain mixture B;

[0055] S3. 53 g of mixture B, 14 g of styrene, 24 g of maleic anhydride and 0.02 g of azobisisobutyronitrile were mixed and heated under reflux at 56 ° C for 3.5 h to obtain a modified polyvinyl pyrrolidone;

[0056] S4. The silicon nitride powder was pickled with a mixed acid of 15 mL nitric acid, 70 mL hydrochloric acid and 15 mL sulfuric acid for 3 h, wherein the acid mass fraction was less than 68%, the hydrochloric acid mass fraction was less than 20%, and the sulfuric acid mass fraction was less than 70%, then washed 3 times with water, filtered and dried at 43 ° C to obtain the treated silicon nitride powder;

[0057] S5. 110 g of the treated silicon nitride powder was mixed with 5 g of alumina, 3.8 g of modified polyvinyl pyrrolidone, 1.5 g of polydimethylsiloxane and 59 g of ethanol and stirred uniformly, and then sent to a sand mill for sand milling, the sand mill speed was set to 760 r / min, and silicon nitride grinding balls with a diameter of 0.62 mm were added, and the sand milling time was 60 min to obtain a mixture C;

[0058] S6. The polyvinyl butyral was dissolved in a toluene-ethanol mixed solution with a volume ratio of 1:5 to obtain a binder, and then the mixture C was fed into a vertical mixer, 8.2 g of the binder and 6 g of phthalate were added, the stirring rate was 500 r / min, the stirring time was 2.5 h, and the slurry was fully stirred to obtain a mixture D;

[0059] S7. The mixture D is sent to an online degassing machine for degassing. The vacuum degree during degassing is 0.3 Pa, the temperature is 50° C., the stirring rate is 650 r / min, and the degassing time is 110 min to obtain silicon nitride slurry.

[0060] Embodiment 3: An automated silicon nitride slurrying process comprising the following steps:

[0061] S1. Add 24 mL of isopropanol and 10 g of 2,2'-azo[2-methyl-N-(2-hydroxyethyl)propionamide] to 1 mol of polyvinylpyrrolidone, and add one third of β-mercaptoethanol at the beginning of the reaction and after 20 minutes and 40 minutes, respectively. The total amount of β-mercaptoethanol is 0.036 mol. Heat and reflux at 85°C for 2.5 hours to obtain a mixture A;

[0062] S2. 22 g of mixture A was mixed with 17 g of S, S′-di(α, α′-dimethyl-α″-acetic acid) trithiocarbonate and 24 g of dicyclohexylcarbodiimide, and heated under reflux at 38° C. for 65 min to obtain mixture B;

[0063] S3. 58 g of mixture B, 14 g of styrene, 25 g of maleic anhydride and 0.025 g of azobisisobutyronitrile were mixed and heated under reflux at 58 ° C for 3.5 h to obtain a modified polyvinyl pyrrolidone;

[0064] S4. The silicon nitride powder was pickled with a mixed acid of 15 mL nitric acid, 70 mL hydrochloric acid and 15 mL sulfuric acid for 3.5 h, wherein the acid mass fraction was less than 68%, the hydrochloric acid mass fraction was less than 20%, and the sulfuric acid mass fraction was less than 70%, then washed 3 times with water, filtered and dried at 48 ° C to obtain the treated silicon nitride powder;

[0065] S5. 120 g of the treated silicon nitride powder was mixed with 7 g of alumina, 4.2 g of modified polyvinyl pyrrolidone, 1.5 g of polydimethylsiloxane and 62 g of ethanol and stirred uniformly, and then sent to a sand mill for sand milling, the sand mill speed was set to 790 r / min, and silicon nitride grinding balls with a diameter of 0.65 mm were added, and the sand milling time was 65 min to obtain a mixture C;

[0066] S6. The polyvinyl butyral was dissolved in a toluene-ethanol mixed solution with a volume ratio of 1:6 to obtain a binder, and then the mixture C was fed into a vertical mixer, 8.5 g of the binder and 6 g of phthalate were added, the stirring rate was 550 r / min, the stirring time was 2.5 h, and the slurry was fully stirred to obtain a mixture D;

[0067] S7. The mixture D is sent to an online degassing machine for degassing. The vacuum degree during degassing is 0.4 Pa, the temperature is 50° C., the stirring rate is 700 r / min, and the degassing time is 115 min to obtain silicon nitride slurry.

[0068] Embodiment 4: An automated silicon nitride slurrying process comprising the following steps:

[0069] S1. Add 25 mL of isopropanol and 10 g of 2,2'-azo[2-methyl-N-(2-hydroxyethyl)propionamide] to 1 mol of polyvinylpyrrolidone, and add one third of β-mercaptoethanol at the beginning of the reaction and after 20 minutes and 40 minutes, respectively. The total amount of β-mercaptoethanol is 0.04 mol. Heat and reflux at 88°C for 3 hours to obtain a mixture A;

[0070] S2. 23 g of mixture A was mixed with 18 g of S, S′-di(α, α′-dimethyl-α″-acetic acid) trithiocarbonate and 25 g of dicyclohexylcarbodiimide, and heated under reflux at 40° C. for 70 min to obtain a mixture B;

[0071] S3. 60 g of mixture B, 15 g of styrene, 26 g of maleic anhydride and 0.03 g of azobisisobutyronitrile were mixed and heated under reflux at 60 ° C for 4 h to obtain a modified polyvinyl pyrrolidone;

[0072] S4. The silicon nitride powder was pickled with a mixed acid of 20 mL nitric acid, 60 mL hydrochloric acid and 20 mL sulfuric acid for 4 h, wherein the acid mass fraction was less than 68%, the hydrochloric acid mass fraction was less than 20%, and the sulfuric acid mass fraction was less than 70%, then washed 3 times with water, filtered and dried at 50 ° C to obtain the treated silicon nitride powder;

[0073] S5. 130 g of the treated silicon nitride powder was mixed with 8 g of alumina, 4.7 g of modified polyvinyl pyrrolidone, 2 g of polydimethylsiloxane and 67 g of ethanol and stirred uniformly, and then sent to a sand mill for sand milling, the sand mill speed was set to 830 r / min, and silicon nitride grinding balls with a diameter of 0.68 mm were added, and the sand milling time was 70 min to obtain a mixture C;

[0074] S6. The polyvinyl butyral was dissolved in a toluene-ethanol mixed solution with a volume ratio of 1:6 to obtain a binder, and then the mixture C was fed into a vertical mixer, 9 g of the binder and 7 g of phthalate were added, the stirring rate was 600 r / min, the stirring time was 3 h, and the slurry was fully stirred to obtain a mixture D;

[0075] S7. The mixture D is sent to an online degassing machine for degassing. The vacuum degree during degassing is 0.5 Pa, the temperature is 55° C., the stirring rate is 800 r / min, and the degassing time is 120 min to obtain silicon nitride slurry.

[0076] Comparative Example 1:

[0077] Compared with Example 1, this comparative example does not add a dispersant during the automated silicon nitride slurry preparation process, and the remaining steps and parameters are the same, which will not be repeated in this comparative example, and finally silicon nitride slurry is obtained.

[0078] Comparative Example 2:

[0079] Compared with Example 1, this comparative example only replaces "modified polyvinyl pyrrolidone" with "polyvinyl pyrrolidone", and the remaining steps and parameters are the same, which will not be repeated in this comparative example, and finally silicon nitride slurry is obtained.

[0080] Comparative Example 3:

[0081] Compared with Example 1, this comparative example only replaces "modified polyvinyl pyrrolidone" with "triethyl phosphate", and the remaining steps and parameters are the same, which will not be repeated in this comparative example, and finally silicon nitride slurry is obtained.

[0082] Comparative Example 4:

[0083] Compared with Example 1, this comparative example only replaces "modified polyvinyl pyrrolidone" with "polyacrylic acid amine", and the remaining steps and parameters are the same, which will not be repeated in this comparative example, and finally silicon nitride slurry is obtained.

[0084] Comparative Example 5:

[0085] S1. Add 20 mL of isopropanol, 10 g of 2,2'-azo[2-methyl-N-(2-hydroxyethyl)propionamide], and 0.03 mol of β-mercaptoethanol to 1 mol of polyvinyl pyrrolidone, and heat under reflux at 80°C for 2 h to obtain a mixture A;

[0086] S2. 20 g of mixture A was mixed with 15 g of S, S′-di(α, α′-dimethyl-α″-acetic acid) trithiocarbonate and 20 g of dicyclohexylcarbodiimide, and heated under reflux at 35-40° C. for 50 min to obtain a mixture B;

[0087] S3. 50 g of mixture B, 13 g of styrene, 22 g of maleic anhydride and 0.01 g of azobisisobutyronitrile were mixed and heated under reflux at 50 ° C for 3 h to obtain a modified polyvinyl pyrrolidone;

[0088] S4. The silicon nitride powder was pickled with a mixed acid of 10 mL nitric acid, 80 mL hydrochloric acid and 10 mL sulfuric acid for 2 h, wherein the acid mass fraction was less than 68%, the hydrochloric acid mass fraction was less than 20%, and the sulfuric acid mass fraction was less than 70%, then washed 3 times with water, filtered and dried at 40 ° C to obtain the treated silicon nitride powder;

[0089] S5. 100 g of the treated silicon nitride powder was mixed with 4 g of alumina, 3.3 g of modified polyvinyl pyrrolidone, 1 g of polydimethylsiloxane, and 55 g of ethanol and stirred uniformly, and then sent to a sand mill for sand milling, the sand mill speed was set to 720 r / min, and silicon nitride grinding balls with a diameter of 0.6 mm were added, and the sand milling time was 55 min to obtain a mixture C;

[0090] S6. The polyvinyl butyral was dissolved in a toluene-ethanol mixed solution with a volume ratio of 1:4 to obtain a binder, and then the mixture C was fed into a vertical mixer, 7.6 g of the binder and 4 g of phthalate were added, the stirring rate was 400 r / min, the stirring time was 2 h, and the slurry was fully stirred to obtain a mixture D;

[0091] S7. The mixture D is sent to an online degassing machine for degassing. The vacuum degree during degassing is 0.1 Pa, the temperature is 45° C., the stirring rate is 600 r / min, and the degassing time is 100 min to obtain silicon nitride slurry.

[0092] Performance Test:

[0093] Slurry impurity content detection:

[0094] The silicon nitride slurries prepared in Examples 1 to 4 and Comparative Examples 1 to 5 were respectively placed in a conical flask, and a mixed acid of nitric acid and hydrochloric acid in a volume ratio of 1:1 was added for digestion, and then cooled to room temperature, filtered and fixed to volume, and finally detected by inductively coupled plasma atomic emission spectrometry;

[0095] Slurry viscosity test:

[0096] Take 20g of the silicon nitride slurry prepared in Example 1-Example 4 and Comparative Example 1-Comparative Example 5 respectively, put them into a ground-mouth sample bottle, and then put them into a constant temperature water tank to ensure that the water temperature reaches 25±1°C to ensure the consistency of the test conditions. Wipe the viscometer test tank and rotor with alcohol cotton and air-dry them. Take the sample bottle out of the constant temperature water tank, adjust the level of the viscometer, put the silicon nitride slurry into the test tank, and fix the rotor at a speed of 10r / min. Turn on the viscometer power supply, start the rotor motor after the digital display is stable, wait for 60 seconds and then stop, read and record the viscosity value, and repeat the test three times to take the average value;

[0097] Raw material utilization test:

[0098] The silicon nitride slurries prepared in Examples 1 to 4 and Comparative Examples 1 to 5 were respectively poured into a containing device for weighing;

[0099] Raw material utilization rate (%) = actual weight of slurry / theoretical weight of slurry × 100%

[0100] Table 1

[0101]

[0102]

[0103] Data Analysis:

[0104] As can be seen from Table 1, the silicon nitride slurry prepared by the present invention has a higher raw material utilization rate. This may be because the modified polyvinyl pyrrolidone, on the one hand, has the dispersing characteristics of polyvinyl pyrrolidone. The imide group contained in polyvinyl pyrrolidone has a strong polarity, exhibits a good adsorption capacity for solid particles, and is widely used in powder dispersion. In addition, polyvinyl pyrrolidone itself has a certain hydrophilicity. By introducing hydrophobic styrene and maleic anhydride segments, the copolymer maintains a certain hydrophilicity while also enhancing its dispersibility in water. On the other hand, the modified polyvinyl pyrrolidone is a block copolymer, and the incompatibility between different blocks thereof can induce self-assembly, thereby improving the dispersibility and stability of the material. By gradually adding β-mercaptoethanol, the molecular weight of the polymer can be effectively controlled, the uniformity and dispersibility of the copolymer can be improved, and the overall fluidity of the silicon nitride slurry can be improved, so that it is not easy to adhere to the wall in various reactors, the loss of raw materials is reduced, and the utilization rate is improved.

[0105] Those skilled in the art should understand that the discussion of any of the above embodiments is merely illustrative and is not intended to imply that the scope of the present invention is limited to these examples. Under the concept of the present invention, the technical features in the above embodiments or different embodiments may be combined, the steps may be implemented in any order, and there are many other variations of the different aspects of the present invention as described above, which are not provided in detail for the sake of simplicity.

[0106] The present invention is intended to cover all such substitutions, modifications and variations that fall within the broad scope of the appended claims. Therefore, any omissions, modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. An automated silicon nitride slurrying process, characterized in that: Including the following raw materials by weight: Silicon nitride powder 100-130 parts, sintering aid 4-8 parts, binder 7.6-9 parts, dispersant 3.3-4.7 parts, defoamer 1-2 parts, solvent 55-67 parts, plasticizer 4-7 parts; The dispersant is modified polyvinyl pyrrolidone; The modified polyvinyl pyrrolidone is prepared from polyvinyl pyrrolidone, beta-mercaptoethanol, S, S'-di(alpha, alpha'-dimethyl-alpha"-acetic acid) trithiocarbonate and styrene.

2. The automated silicon nitride slurrying process according to claim 1, characterized in that: The particle size of the silicon nitride powder is 1.6-3.3 μm; The sintering aid is at least one of aluminum oxide, yttrium oxide, magnesium oxide, calcium oxide and magnesium silicon nitrogen; The solvent is at least one of ethanol, ethylene glycol, isopropanol, n-butanol, and 2-butanone; The binder is selected from at least one of polyethylene glycol, polyvinyl butyral, and methyl acrylate; The plasticizer is any one of phthalate, polyethylene glycol and glycerol; The defoaming agent is any one of fatty alcohol polyoxyethylene ether, alkylphenol polyoxyethylene ether and polydimethylsiloxane.

3. The automated silicon nitride slurrying process according to claim 1, characterized in that: The preparation method of the modified polyvinyl pyrrolidone is as follows: Step A1. Add isopropanol and 2,2'-azo[2-methyl-N-(2-hydroxyethyl)propionamide] to polyvinyl pyrrolidone, and add one-third of β-mercaptoethanol at the beginning of the reaction and after 20 minutes and 40 minutes, respectively, and heat under reflux at 80-88°C for 2-3 hours to obtain a mixture A; Step A2. Mix the mixture A with S, S′-di(α, α′-dimethyl-α″-acetic acid) trithiocarbonate and dicyclohexylcarbodiimide, and heat under reflux to obtain a mixture B; Step A3. Mix mixture B, styrene, maleic anhydride and azobisisobutyronitrile, and heat under reflux at 50-60° C. for 3-4 hours to obtain modified polyvinyl pyrrolidone.

4. The automated silicon nitride slurrying process according to claim 3, characterized in that: The usage ratio of polyvinyl pyrrolidone, isopropanol, 2,2'-azo[2-methyl-N-(2-hydroxyethyl)propionamide] and β-mercaptoethanol in step A1 is 1 mol: 20-25 mL: 10 g: 0.03-0.04 mol.

5. The automated silicon nitride slurry making process according to claim 3, characterized in that: In step A2, the mass ratio of the mixture A to S,S′-di(α,α′-dimethyl-α″-acetic acid) trithiocarbonate and dicyclohexylcarbodiimide is 20-23:15-18:20-25; The temperature during the heating reflux is 35-40° C. and the time is 50-70 min.

6. The automated silicon nitride slurry making process according to claim 3, characterized in that: The mass ratio of the mixture B, styrene, maleic anhydride and azobisisobutyronitrile in step A3 is 50-60:13-15:22-26:0.01-0.

03.

7. The automated silicon nitride slurry making process according to claim 1, characterized in that: The automated silicon nitride slurry making process comprises the following steps: Step S1. The silicon nitride powder is pickled with a mixed acid of nitric acid, hydrochloric acid and sulfuric acid for 2-4 hours, then washed with water three times, filtered and dried at 40-50°C to obtain the treated silicon nitride powder; Step S2. The treated silicon nitride powder is mixed with a sintering aid, a dispersant, a defoaming agent, and a solvent and stirred evenly, and then sent to a sand mill for sand grinding to obtain a mixture C; Step S3. dissolving polyvinyl butyral in a toluene-ethanol mixed solution with a volume ratio of 1:4-6 to obtain a binder, then feeding the mixture C into a vertical mixer, adding the binder and the plasticizer, setting the stirring parameters, and fully stirring the slurry to obtain a mixture D; Step S4: sending the mixture D into an online degassing machine for degassing to obtain silicon nitride slurry.

8. The automated silicon nitride slurry making process according to claim 7, characterized in that: In step S1, the volume ratio of nitric acid, hydrochloric acid and sulfuric acid is 10-20:60-80:10-20; The mass fraction of the nitric acid is less than 68%, the mass fraction of the hydrochloric acid is less than 20%, and the mass fraction of the sulfuric acid is less than 70%.

9. The automated silicon nitride slurry making process according to claim 7, characterized in that: The speed of the sand mill in step S2 is 720-830 r / min; During the sand grinding, silicon nitride grinding balls with a diameter of 0.6-0.68 mm are added, and the sand grinding time is 55-70 minutes.

10. The automated silicon nitride slurry making process according to claim 7, characterized in that: The stirring parameters in step S3 include a stirring rate of 400-600 r / min and a stirring time of 2-3 h; The vacuum degree during degassing in step S4 is 0.1-0.5 Pa, the temperature is 45-55° C., the stirring rate is 600-800 r / min, and the degassing time is 100-120 min.